The mature portion of Escherichia coli maltose-binding protein (MBP) determines the dependence of MBP on SecB for export. - Gannon, P M (1989)
The product of the secB gene is required for export of a subset of secreted proteins to the outer membrane and periplasm of Escherichia coli. Precursor maltose-binding protein (MBP) accumulates in the cytoplasm of secB-carrying mutants, but export of alkaline phosphatase is only minimally affected by secB mutations. When export of MBP-alkaline phosphatase hybrid proteins was analyzed in wild-type and secB-carrying mutant strains, the first third of mature MBP was sufficient to render export of the hybrid proteins dependent on SecB. Substitution of a signal sequence from a SecB-independent protein had no effect on SecB-dependent export. These findings show that the first third of mature MBP is capable of conferring export incompetence on an otherwise competent protein.